Manajemen Pendidikan Islam Non-Formal dalam Menangkal Radikalisme: Studi Kasus PKPNU di PCNU Bangil - Muchammad Rochim; Darim, Abu (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2025)
Purpose: This study aims to examine the management of the Nahdlatul Ulama Branch Board (PCNU) Bangil in countering radicalism through the Pendidikan Kader Penggerak Nahdlatul Ulama (PKPNU) program. It focuses on how PKPNU functions as an ideological and educational movement that strengthens the spirit of Ahlussunnah wal Jamaah An-Nahdliyah and fosters national commitment among NU cadres in PCNU Bangil, Pasuruan Regency, East Java. Design/methodology/approach: This research employed a qualitative approach using a case study design. Data were collected through observation, interviews, and documentation. Primary data were obtained from NU leaders, PKPNU instructors, and alumni in the PCNU Bangil area, while secondary data were derived from institutional planning documents, strategic programs, and archives related to the PKPNU implementation. Data analysis followed the Miles and Huberman model, involving data reduction, data display, and conclusion drawing/verification. Research limitations/implications: The study was limited by the scope of research focusing on one regional NU branch, which may not fully represent other regions’ management practices. Future studies could compare multiple NU branches to enrich the understanding of PKPNU’s role in countering radicalism at a broader scale. Findings: The findings indicate that: (1) at the planning level, PCNU Bangil is strongly committed to preventing radicalism through PKPNU, as reflected in its strategic documents and priority programs; (2) at the implementation level, PKPNU serves as an effective ideological reinforcement tool that transforms NU’s values into social and national awareness; and (3) in the evaluation phase, the organization recognizes the need for post-program monitoring to maintain cadres’ ideological consistency and vigilance against both internal and external radical influences. Originality/value: This research provides empirical evidence on how PKPNU functions as a strategic model of ideological education within Nahdlatul Ulama to safeguard the Islamic moderate tradition (Aswaja An-Nahdliyah) and strengthen national resilience. It contributes to the discourse on religious moderation and deradicalization efforts led by civil society organizations in Indonesia.